A Fatal Outcome of SARS-COV-2 Infection: A Case Report of A 60 Years Old Man with Multiple Organ Failure - Ridwan, Muhammad; Yunita, Elvira (Sang Pencerah: Jurnal Ilmiah Universitas Muhammadiyah Buton, 2022)
The infection of Corona Virus Disease – 19 (COVID-19) has spread out in Indonesia. The number of deaths has increased in recent months. Cases of infection are followed by comorbidities such as diabetes, hypertension, cardiovascular and cerebrovascular condition have higher risk to develop severe illness. These conditions also give the higher risk of death in patients. Herein, we reported a 60 years old man that was infected with Sar-Cov-2 and had no comorbidities. Before the infection, patient was healthy. In the early phase of infection, clinical manifestations were seen in patients such as fever, cough, nausea and vomiting. A few days after being admitted to the hospital, the condition began to get worse which led to multiple organ failure. Acute kidney injury, liver injury, dysregulation of glucose level and acid base disorder were shown from laboratory tests. Unfortunately, clinical manifestations were poor and the patient passed away.